1984
DOI: 10.1111/j.1365-2125.1984.tb02592.x
|View full text |Cite
|
Sign up to set email alerts
|

The role of digitalis in the future.

Abstract: Cardiac glycosides exert an acute positive inotropic effect on the normal and failing heart. Recent evidence establishes that the positive inotropic effect is maintained over several months in many patients. The effectiveness of long‐term treatment with cardiac glycosides in relieving symptoms is less certain; only a small subset of patients benefits. An effect on mortality is not established. The use of digoxin in the treatment of mild heart failure is questionable since the drug has serious side‐effects and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
1

Year Published

1988
1988
1991
1991

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 51 publications
0
4
1
Order By: Relevance
“…This conclusion differed from the find ings of many studies undertaken to deter mine whether digoxin was efficacious [8,11]. In general, these studies were not ran domized, double-blind or placebo-controlled trials.…”
Section: Evidence For Efficacy Of Digoxincontrasting
confidence: 50%
See 1 more Smart Citation
“…This conclusion differed from the find ings of many studies undertaken to deter mine whether digoxin was efficacious [8,11]. In general, these studies were not ran domized, double-blind or placebo-controlled trials.…”
Section: Evidence For Efficacy Of Digoxincontrasting
confidence: 50%
“…MacKenzie [6] and Lewis [7] emphasized the value of digoxin in patients with atrial fibrillation. The use of the drug in sinus rhythm was and is contro versial [8].…”
Section: Evidence For Efficacy Of Digoxinmentioning
confidence: 99%
“…The first detailed description of cardiac glycosides by William Withering was published in 1785 [7]. Numerous historical and medical reviews have been written recently [1,2,5,[8][9][10][11][12].…”
Section: Historymentioning
confidence: 99%
“…Several studies early this century reported that glycosides were effective in patients with heart failure and sinus rhythm [15][16][17], whilst Sir James MacKenzie and Sir Thomas Lewis, at least in his earlier work, were skeptical. This doubt has persisted to the present time and has resulted in many studies of the problem, using a variety of techniques and study designs [1,2,11]. The introduction of diuretics over 30 years ago [18] revolutionized the treatment of heart failure.…”
Section: Historymentioning
confidence: 99%
See 1 more Smart Citation